Technological Determinism, New Literacies And Learning Process And The Impact Towards Future Learning - Harisa Mardiana; Haris Kaisar Daniels (Universitas Negeri Makassar, 2019)
The interest of this research is to investigate technological change, new literacies and learning processes which impact future learning. With technological determinism, the members of the university need to have technological knowledge, belief of change and adopt the technology. The problem in this research is the habits in the individual who works within our campus that would not change, because with the new literacies used and introduced in communication, besides learning in using online systems will continue to be implemented. The research sampling is conducted of 76 respondents, consisting of students, lecturers, employees, staff and technicians. And this research method uses is quantitative methods and semi-structured qualitative methods. The result obtained that there are members of campus who are willing to change in communication and the ways of thinking and acting to follow the change in future learning 4.0 industrial revolutions